Lansia Sebagai Pekerja Informal Di Maluku: Pengaruh Karakteristik Individu terhadap Kesempatan Kerja - Italia Sandi; Rabina Yunus; Sakaria Anwar (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2022)
The aging population will become a burden for the society, including countries, especially because of the limitations of the current social security system, requiring the elderly to meet their own needs. However, due to the limited number of jobs that are available and able to be entered by the elderly, the majority of workers are absorbed in the informal sector with vulnerable and low-income types of work. The purpose of this research is to get an overview about the elderly workers characteristics in Maluku and their effect on the type of economic activity they had. The data that used in this study is sourced from Sakernas August 2021 with analytical methods using descriptive analysis and Binary Logistics Regression. Research variables derived from individual characteristics possessed by elderly workers, consisting of gender, type of residence area, education and training participation. The results showed that all variables used in this study had a significant effect on the existence of the elderly who were informal workers. More than half of the elderly population who work in Maluku are men. However, older women are more likely to be informal worker. In addition to those who are female, the elderly who have a bigger chance to becoming informal workers are those who live in rural areas, do not go to school, and have never attended training/courses. The biggest tendency to become elderly as informal workers is owned by the elderly who have never attended training/courses, so to improve the quality of elderly workers to have more decent job can be done by conducting training.